Pengaruh Profesionalisme dan Inovasi terhadap Kualitas Pelayanan Publik - Mokoagow, Gia; Rahmisyari, Rahmisyari; Sabir, Muh. (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to analyze the influence of civil servant professionalism and social media innovation on the quality of public services at the Department of Communication and Informatics of Bolaang Mongondow Selatan Regency. Bureaucratic reform in Indonesia demands improvements in public service quality that are responsive, efficient, and transparent. This research adopts a quantitative approach using a survey method involving 310 respondents who follow the Instagram account @diskominfobolsel. The independent variables examined are professionalism (consisting of equality, equity, loyalty, and accountability) and social media innovation (including accessibility, efficiency, responsiveness, and transparency), while the dependent variable is public service quality. The results of multiple linear regression analysis show that professionalism and social media innovation simultaneously have a significant effect on public service quality. Partially, both professionalism and social media innovation have a positive and significant influence. This study highlights the importance of enhancing the capacity of human resources and optimizing the use of social media platforms such as Instagram to support e-government-based public services. These findings serve as an important reference for developing adaptive public service strategies in response to technological dynamics and public demands.